Model of quality management in higher business schools - Škafar, Branko (Anali PAZU, 2022)
In this paper a genuine model of the quality management system at the higher vocational colleges is introduced.  The model is called the System Requirements of the Quality Management at the Vocational Colleges. The model itself has been prepared under the IMPLETUM project, Aktivnosti 9 Kakovost (Activities 9 Quality). The requirements are based on contemporary standards and the model of quality management where, among the basic requirements, a requirement for fulfilling the actual legislation and implementing the guide lines into the higher vocational education is stressed. The model has also been tested in the real situation. There were 60 higher vocational colleges in the school year of 2010/11 in Slovenia, of which 40 have used the system introduced in this paper. The results of the evaluation on how the application of the System Requirements of the Quality Management at the Vocational Colleges model is beneficial to the users have been gained with a survey. The survey included 30 schools and the results have been presented in this paper.
Keywords: model; quality; requirements of the quality management at higher vocational colleges